Pengaruh Karakteristik Pemerintah Daerah Dan Temuan Audit Bpk Terhadap Kinerja Pemerintah Daerah Di Indonesia (Studi Empiris Pada Pemerintah Daerah Kabupaten/Kota Di Indonesia) - Susilowati, Ponco, Drs.Atwal Arifin, Akt.,M.Si (2016)
This research analyzes the influence of size , level of wealth , degree of dependence , capital expenditures , and audit findings by Financial oversight Agency, in Indonesian's name (BPK) toward the performance of local government as one of the public sector organizations. The population is local governments who made Local Governance Processes Reports (LPPD) during 2013. The chosen sample is done using purposive sampling. This sample is used by 263 local governments around Indonesia. The used Data analysis method is descriptive statistics and hypothesis testing using multiple linear regressions. The result shows that the size of the local government and variable of Capital expenditure does not have a significant effect on the performance of local governments. The level of wealth, intergovernmental revenue and audit findings has significant effect toward the performance of local governments. it shows that there is a negative relation between audit finding and financial performance of local government. Thus, the greater the findings of the audit will determine the financial performance of local governments